Metabolomics flux on the genome scale - Cascante, Marta; Marín de Mas, Igor (Henry Stewart Talks, 2018)
Modeling in systems biology, Computational metabolic modeling types, Constraint-based metabolic modeling, CBM & GSMM, Principles of flux balance analysis (FBA), Flux variability analysis (FVA), Data integration, Kinetic modeling, Computational modeling examples